Bakti Sosial Pengabdian Masyarakat melalui Sunat Massal Gratis di Klinik Swara Medika Medan Sumatera Utara - Rahman Aceh, Arif; Munir, Chairul; Matondang, Elsa Rizky Safitri; Purba, Jesmo Aldoran (Cattleya Darmaya Fortuna, 2023)
Circumcision is one of the teachings of Prophet Ibrahim AS which is an obligation for men. Klink Swara Medika Circumcision Volunteer Team partnering with DPD PPNI Medan City to provide free mass circumcision assistance for children in this community service social service event during the school holidays in accordance with the health protocol. The purpose of this mass circumcision social service activity is to mass circumcise Muslim children who are about to reach puberty in the Medan environment, especially children who are economically disadvantaged. The method used in this activity is to disseminate information on community service activities through direct visits to the Swara Medika Clinic in Medan City, social media. The result of this community service activity was that mass circumcision was carried out on July 2, 2023 at the Swara Medika Clinic in Medan City. Participants in the mass circumcision were 20 people from various sub-districts of Medan City. There were 8 medical personnel involved and 8 medical assistant assistants from the Regional Representative Council of the Indonesian National Nurses Association in Medan City.